Distribution of mangrove species reported as rare in Andaman and Nicobar islands with their taxonomical notes - PANDISAMY RAGAVAN; K. RAVICHANDRAN; R. S.C. JAYARAJ; P. M. MOHAN; ALOK SAXENA; S SARAVANAN; A. VIJAYARAGHAVAN (Biodiversitas Journal of Biological Diversity, 2014)
Ragavan P, Ravichandran K, Jayaraj RSC, Mohan PM, Saxena A, Saravanan S, Vijayaraghavan A. 2014. Distribution of mangrove species reported as rare in Andaman and Nicobar islands with their taxonomical notes. Biodiversitas 15: 12-23. During the recent field survey it was found that among 15 rare mangroves in Andaman and Nicobar Islands, ten rare species i.e. Acanthus ebracteatus, Acrostichum speciosum, Bruguiera cylindrica, Cynometra iripa, Cynometra ramiflora, Lumnitzera racemosa, Rhizophora hybrids, Sonneratia alba, Sonneratia griffithii and Xylocarpus mekongensis are present in Andaman and Nicobar islands. In addition to Acanthus volubilis, Brownlowia tersa and Sonneratia ovata are recorded after their first report.